Effects of switching from MiniMed™ 640G to 770G on continuous glucose monitoring metrics and DTR‐QOL scores: An observational study of Japanese people with type 1 diabetes mellitus - Toshiki Kogai; Junko Sato; Haruna Yasuda; Tatsuhiro Ayame; Azusa Ozaki; Eri Takagi; Mami Koshibu; Yuya Nishida; Fuki Ikeda; Hirotaka Watada (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction We evaluated the effect of the MiniMed™ 770G, an insulin pump using hybrid closed‐loop technology, on blood glucose management and quality of life in Japanese people with type 1 diabetes. Materials and Methods This was a 52‐week, prospective, observational study. Fifty Japanese people with type 1 diabetes switched from the MiniMed™ 640G to 770G, and we analyzed the continuous glucose monitoring data of 24 subjects who used auto mode throughout the study. We also analyzed the scores of the Diabetes Therapy‐Related Quality of Life questionnaire completed by 26 auto‐mode users before and after the treatment change. Results The baseline time in range 70–180 mg/dL was 67.3 (54.8–78.4)%, with a significant improvement beginning 8 weeks after the switch and lasting until 52 weeks. The baseline time below range <70 mg/dL was 1.9 (0.6–3.6)%, with a significant increase at week 8; however, the mean value was less than 4% throughout the study period. On the other hand, the number of blood glucose measurements significantly increased. While there was no significant difference in the overall change in the total Diabetes Therapy‐Related Quality of Life score, there was a significant decrease in the treatment satisfaction score. Conclusions Use of the MiniMed™ 770G improved continuous glucose monitoring metrics. However, treatment satisfaction decreased, probably due to the increased frequency of blood glucose monitoring necessary to maintain auto mode.